Achieving Sustainable Tourism through Payment for Ecosystem Service (PES) Program: Case Study of Marine Tourism in Gili Matra Indonesia - Diswandi, Diswandi; Fadliyanti, Luluk; Afifi, Mansur; Hailuddin, Hailuddin (Jurnal Ekonomi & Studi Pembangunan, 2021)
Harmonization of tourism and conservation activities can be used to achieve sustainable tourism. Regarding this matter, the Payment for Ecosystem Services (PES) program could be a promising solution to be implemented. By considering marine tourism in Gili Matra, Lombok, this study applied quantitative research method to analyzed the possibility of sustainable tourism development through the PES scheme for harmonizing marine tourism and preserve coral reefs. Data was collected thorugh survey to 100 international tourists that were selected randomly. Using the Contingent Valuation Method (CVM), this study found that international tourists were willing to pay an average of USD 21.46 per visit to contribute to the PES program to sustain the existence of coral reefs and other marine biotas as ecosystem services provided by Gili Matra. The tourists’ educational and income levels influenced their willingness to pay.